Rainwater harvesting the collection of rainfall and runoff in rural areas - Pacey,Arnold (London Intermediate Technology Publication, 1986)
This book emphasizes the importance of social, economic, and environmental considerations when planning and implementing projects. For rural development workers, it aims to fill the gap in existing literature on the gathering and storage of water.
Includes Index
Keywords: Rainwater Harvesting